STRATEGY OF PROFESSIONAL SUPERVISION FOR THE PREPARATION AND PUBLICATION OF SCIENTIFIC ARTICLES - Armiñana-García, Rafael (2021)
Research as a process of confi rmation or refutation of assumptions, theories, phenomena, and others is important because it makes it possible to place an area of knowledge at the forefront, demonstrating what is useful and what is not. The main objective of this research is to propose a professional improvement strategy to contribute to the development of skills in the elaboration and subsequent publication of scientifi c articles in high-impact indexed journals. For the development of the research, methods of information gathering and processing were used, to use them in a multilateral way in the study of the object; within the latter, observation and interview stood out. Th e sample consisted of 12 professors intentionally selected from diff erent departments of the Pedagogical Sciences on the “Felix Varela Morales” campus of the “Marta Abreu” Central University of Las Villas. Th e results confi rmed the defi ciencies that some professors have in the elaboration and subsequent accreditation of scientifi c articles in indexed journals. Th ese results served as the basis to design and propose this strategy, which was submitted to criteria by experts who valued it as pertinent. Once the proposal was implemented, the 12 professors, as authors and co-authors, managed to accredit at least one scientific article in a high-impact indexed journal. These results show the relevance of the Professional Development Strategy developed.